Quantum chemical studies on molecular structure, spectroscopic (IR, Raman, UV-Vis), NBO and HOMO-LUMO analysis of 1-benzyl-3-(2-furoyl) thiourea - Gil, Diego Mauricio (2015)
Vibrational and electronic spectra for 1-benzyl-3-(2-furoyl) thiourea were calculated by using density functional method (B3LYP) with different basis sets. The complete assignment of all vibrational modes was performed on basis of the calculated frequencies and comparing with the reported IR and Raman spectra for that thiourea derivative. UV-visible absorption spectra of the compound dissolved in methanol were recorded and analyzed using time dependent density functional theory (TD-DFT). The calculated values for the geometrical parameters of the title compound are consistent with the ones reported from XRD studies. The stability of the molecule, related to hyper-conjugative interactions, and electron delocalization were evaluated using natural bond orbital (NBO) analysis. Intramolecular interactions were studied by AIM approach. The HOMO and LUMO analysis are used to determine the charge transfer within the molecule. Molecular electrostatic potential map was performed by the DFT method.